Development and Modification in the use of Land in the former Industrial Workshops Area in North of Jeddah - Al-Shareef, Amal Mohammed; Al-Sulami, Morshed Moayed (Journal of Humanities & Social Sciences, 2022)
This study deals with the change of land use in the Industrial Workshops area in North of Jeddah during the period (2015- 2019). This study aims to know the changes in the use of the land, the detection of environmental damage and problems, the identification of the characteristics of the area after the removal of the industrial workshops, and the development of proposals to develop the study area based on the Vision of the year 2030.This research relied on the descriptive approach to describe the changes in the study area, and the study contained four chapters. The first chapter dealt with the theoretical framework of the study, and the second chapter has the characteristics, the features, and the development of population growth in the study area. The third chapter dealt with changes in the land uses in the study area and the construction system, while the fourth chapter dealt with the conclusion, the results, and the recommendations.The results of the study proved that the growth spurt of the city of Jeddah led to the intersection in the different uses of the land as it is in the industrial workshop area with residential uses. It confirmed that the external appearance of the industrial workshops that constitute of (18.22%) of the total area that harm the civilized appearance of Jeddah (The Researcher). The study also displays the transfer of industrial workshops from the south of King Abdulaziz International Airport to the Asfan industrial area. The study proved that there is a conflict between the land owners and Jeddah Municipality over the current uses in the region.The study recommended preparing modern design standards to implement the area development plan, and to involve service authorities in implementing water, electricity and sanitation networks. In addition to the need for team work between the landowners and the government agencies involved in the developing of the study area.
Keywords: Land use; Industrial workshops; Nozha district; Asfan industrial